2012
DOI: 10.3892/ol.2012.1040
|View full text |Cite
|
Sign up to set email alerts
|

rs12976445 variant in the pri-miR-125a correlates with a lower level of hsa-miR-125a and ERBB2 overexpression in breast cancer patients

Abstract: Expression of MIR125A is diminished in breast tumors, however the reason for the hsa-mir-125a decrease in the cancer is not known. HER2 is encoded by ERBB2, a target for hsa-miR-125a which interacts with the 3′UTR of ERBB2 mRNA. The present study reveals that a polymorphism (rs12976445) within the pri-miR-125a sequence correlates with the amount of mature hsa-miR-125a in breast tumor samples. miRNA, RNA and DNA were extracted from breast cancer samples obtained from 26 patients. Following immunohistological ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 17 publications
1
34
1
Order By: Relevance
“…Our data indicate that the C allele and CC genotype are correlated with HD development and GD intractability ( Tables 5 and 6). A previous study reported that C allele carriers (CC + CT genotypes) correlated with low miR-125a expression compared with the TT genotype in a Polish population [23]. However, in the present study, the association between genotype and miR-125a expression level was not observed in control subject PBMCs (Fig.…”
Section: Discussioncontrasting
confidence: 72%
“…Our data indicate that the C allele and CC genotype are correlated with HD development and GD intractability ( Tables 5 and 6). A previous study reported that C allele carriers (CC + CT genotypes) correlated with low miR-125a expression compared with the TT genotype in a Polish population [23]. However, in the present study, the association between genotype and miR-125a expression level was not observed in control subject PBMCs (Fig.…”
Section: Discussioncontrasting
confidence: 72%
“…6 Currently, multiple miRNAs are known to participate in regulating the proliferation, differentiation, metabolism, and apoptosis of tumor cells. [14][15][16] The study has revealed that miR-125b controls proliferation and apoptosis by downregulating P53 and the genes involved in the P53 pathway including BAK1 and PUMA, which provides for the first time a potential mechanism for the development of secondary hematologic malignancies in patients treated with IMiD compounds. 9,10 Studies have shown that miR-125b acts as a tumor-suppressor gene in chronic lymphocytic leukemia (CLL) and MM, 11,12 whereas miR-125a is a newly discovered member of miR-125, whose precursor can produce two kinds of mature miR-125a-3p and miR-125a-5p, 13 which have also been reported to be tumorsuppressor genes in various malignant tumors, such as prostate tumor, lung tumor, and ovarian tumor.…”
mentioning
confidence: 99%
“…Two polymorphisms in the miR‐125a gene are associated with breast cancer (Li et al , ; Lehmann et al , ). The variants lead to decreased levels of mature miR‐125a and upregulation of its target ERBB2 (Duan et al , ; Lehmann et al , ).…”
Section: Non‐coding Rnasmentioning
confidence: 99%